Bone marrow evaluation of patients having pancytopenia at tertiary care center, M. Y. hospital, Indore, India: one-year study - Mittal, Meena; Kulkarni, C.V.; Likhar, Khushboo (International Journal of Research in Medical Sciences, 2019)
Background: Pancytopenia is reduction of all three formed elements of blood below the normal reference range leading to anemia, leucopenia, thrombocytopenia. Bone marrow aspiration is extremely helpful in evaluating the cause of pancytopenia by cellularity and cytology in order to prevent grave complications and mortality as the underlying pathology determines the management and prognosis of the patients. Aim of research study was to evaluate the patients having pancytopenia at tertiary care center, M.Y.H. Hospital, Indore, India. Methods: The present study was carried out over a period of one year from 2017 to 2018, in the Department of Pathology, M. Y. Hospital, Indore. During this period, a total of 109 bone marrow smears were examined. Out of these, 42 cases had the clinical presentation of pancytopenia. A detailed study was done regarding clinical examination and hematological and radiological investigations. Results: In this study 42 cases of pancytopenia were examined over a period of one year. The commonest cause of pancytopenia was megaloblastic anemia (33.34%) followed by aplastic anemia (19.05%). Others includes myelodysplastic syndrome (MDS), acute leukemia, erythroid hyperplasia and plasmacytosis. Conclusions: Bone marrow aspiration can diagnose majority of the cases of pancytopenia. Megaloblastic anemia and aplastic anemia are the commonest causes of pancytopenia.